2016
DOI: 10.1255/jnirs.1213
|View full text |Cite
|
Sign up to set email alerts
|

LOCAL Regression Algorithm Improves near Infrared Spectroscopy Predictions When the Target Constituent Evolves in Breeding Populations

Abstract: The CGIAR Harvest Plus Challenge Program began in the mid-2000s to support the genetic improvement of nutritional quality in various crops, including the carotenoids content of cassava roots. Successful conventional breeding requires a large number of segregating progenies. However, only a few samples can be quantified by high performance liquid chromatography each day for total carotenoids (TCC) and b-carotene (TBC) contents, limiting the gains from breeding. This study describes the usefulness of near infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…The availability of irrigation at CIAT reduced the difference in dry and wet season, but only partially. As the problem of a lengthy harvesting season became evident, CIAT began the development of the protocol for predicting pVAC and DMC based on NIRS, as described above [82,84]. The possibility of selecting for high pVAC based on reliable NIRS predictions was a major breakthrough.…”
Section: Evolution and Improvements Of Breeding Methods To Increase Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of irrigation at CIAT reduced the difference in dry and wet season, but only partially. As the problem of a lengthy harvesting season became evident, CIAT began the development of the protocol for predicting pVAC and DMC based on NIRS, as described above [82,84]. The possibility of selecting for high pVAC based on reliable NIRS predictions was a major breakthrough.…”
Section: Evolution and Improvements Of Breeding Methods To Increase Cmentioning
confidence: 99%
“…Spectra were corrected for light scattering using the standard normal variate and de-trend (SNVD) correction. Then, the second derivative of the Log(1/R) spectrum, calculated on five data points and smoothed using Savitzky-Golay polynomial smoothing on five data points, was used in combination with LOCAL regressions to develop prediction models [84].…”
Section: Evolution and Improvements Of Quantifying Protocols For Caromentioning
confidence: 99%
“…However, they tend to overestimate carotenoid content when compared to HPLC due to other compounds also detected [21,22]. Near-infrared spectrometry (NIRS) has proven a costand time-efficient method for high-throughput screening for carotenoid content in sweet potato [23], banana [24,25], and cassava as well as for other important breeding traits such as dry matter content (DMC) and cyanogenic potential [26,27,28]. New portable devices such as iCheck and portable NIRS are being evaluated and show promise for use in the field when transport of fresh cassava roots to the nearest laboratory is a challenge [29].…”
Section: Provitamin a Carotenoidsmentioning
confidence: 99%
“…Data used in this study for assessing the proposed local method come from a breeding program (Harvest Plus Challenge Program) on cassava plants monitored by the International Center for Tropical Agriculture in Colombia . One objective of the program was to study and improve the nutritive quality of the cassava roots (see Davrieux et al for details).…”
Section: Methodsmentioning
confidence: 99%
“…The present study focused on the total β-carotene content (TBC). Due to breeding improvements, the mean content of TBC increased slowly from 2009 to 2012, but a significant increase appeared in 2013, by which time the mean was 3 points higher than in 2009, 26 as shown in Table 1. Because of an increasing TBC content year after year, Davrieux et al showed the limitation of the usual global PLSR approach and got better predictions using a local PLSR.…”
Section: Data Setmentioning
confidence: 99%